Brain Activation during Thoughts of One's Own Death and Its Linear and Curvilinear Correlations with Fear of Death in Elderly Individuals: An fMRI Study. Issue 1 (28th January 2021) - Hirano, Kanan; Oba, Kentaro; Saito, Toshiki; Yamazaki, Shohei; Kawashima, Ryuta; Sugiura, Motoaki
Abstract: Facing one's own death and managing the fear of death are important existential issues, particularly in older populations. Although recent functional magnetic resonance imaging (fMRI) studies have investigated brain responses to death-related stimuli, none has examined whether this brain activation was specific to one's own death or how it was related to dispositional fear of death. In this study, during fMRI, 34 elderly participants (aged, 60–72 years) were presented with either death-related or death-unrelated negative words and asked to evaluate the relevance of these words to the "self" or the "other." The results showed that only the left supplementary motor area (SMA) was selectively activated during self-relevant judgments of death-related words. Regression analyses of the effect of fear of death on brain activation during death-related thoughts identified a significant negative linear correlation in the right supramarginal gyrus (SMG) and an inverted-U-shaped correlation in the posterior cingulate cortex (PCC) only during self-relevant judgments. Our results suggest potential involvement of the SMA in the existential aspect of thoughts of death. The distinct fear-of-death-dependent responses in the SMG and PCC may reflect fear-associated distancing of the physical self and the processing of death-related thoughts as a self-relevant future agenda, respectively.